Prognostic value of CA 19-9, CEA, CRP, LDH and bilirubin levels in locally advanced and metastatic pancreatic cancer: results from a multicenter, pooled analysis of patients receiving palliative chemotherapy - Haas, Michael; Heinemann, Volker; Kullmann, Frank; Laubender, Rüdiger P.; Klose, Christina; Bruns, Christiane J.; Holdenrieder, Stefan; Modest, Dominik P.; Schulz, Christoph; Boeck, Stefan (Journal of cancer research and clinical oncology, 2013)
Purpose CA 19-9 is the only established tumor marker in pancreatic cancer (PC); the prognostic role of other serum markers like CEA, CRP, LDH or bilirubin has not yet been defined. Methods We pooled pre-treatment data on CA 19-9, CEA, CRP, LDH and bilirubin levels from two German multicenter randomized phase II trials together with prospective patient data from one high-volume German Cancer Center. Marker levels were assessed locally before the start of palliative first-line therapy for advanced PC and serially during treatment (for CA 19-9 only). Clinical and biomarker data (overall 12 variables) were correlated with the efficacy endpoints time-to-progression (TTP) and overall survival (OS) by using uni- and multivariate Cox models. Results Data from 291 patients were included in this pooled analysis; 253 patients (87 %) received treatment within prospective clinical trials. Median TTP in the study cohort was 5.1 months and median OS 9.0 months. In univariate analysis, pre-treatment CA 19-9 (HR 1.55), LDH (HR 2.04) and CEA (HR 1.89) levels were significantly associated with TTP. Regarding OS, baseline CA 19-9 (HR 1.46), LDH (HR 2.07), CRP (HR 1.69) and bilirubin (HR 1.62) were significant prognostic factors. Within multivariate analyses, pre-treatment log [CA 19-9] (as continuous variable for TTP) and log [bilirubin] as well as log [CRP] (for OS) had an independent prognostic value. A CA 19-9 decline of ≥25 % during the first two chemotherapy cycles was predictive for TTP and OS, independent of the applied CA 19-9 assay. Conclusion Baseline CA 19-9 and CA 19-9 kinetics during first-line chemotherapy are prognostic in advanced PC. Besides that finding other serum markers like CRP, LDH and bilirubin can also provide prognostic information on TTP and OS.